The impact of video speed on the estimation of time duration in sport - Schütz, Lisa-Marie; Schweizer, Geoffrey; Plessner, Henning (Journal of sport & exercise psychology, 2021)
The authors investigated the impact of video speed on judging the duration of sport performance. In three experiments, they investigated whether the speed of video presentation (slow motion vs. real time) has an influence on the accuracy of time estimation of sporting activities (n1 = 103; n2 = 100; n3 = 106). In all three studies, the time estimation was more accurate in real time than in slow motion, in which time was overestimated. In two studies, the authors initially investigated whether actions in slow motion are perceived to last longer because the distance they cycled or ran is perceived to be longer (n4 = 92; n5 = 106). The results support the hypothesis that the duration of sporting activities is estimated more accurately when they are presented in real time than in slow motion. Sporting officials’ judgments that require accurate time estimation may thus be biased when based on slow-motion displays.
Gesehen am 15.10.2021